2021
DOI: 10.1177/11206721211000648
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management and outcomes of pediatric open globe injuries requiring vitrectomy

Abstract: Purpose: To describe surgical management and establish visual outcomes of open globe injury (OGI) in pediatric patients requiring vitrectomy. Methods: Forty-eight eyes of 48 pediatric patients underwent vitrectomy for OGI with secondary vitreoretinal complications in the eye center of Jilin University were included. Characteristics of patients, details of ocular examination and operation, presenting and final visual acuity were recorded. Results: Presenting visual acuity less than 20/400 was found in 44 eyes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…While the rate of second surgery in Shah MA, et al 2013 [48] study was 30%. While Liu, X et al 2022 [49] reported that traumatic cataract was found in 29 (60.4%). 8.3% had one operation (vitrectomy to remove IOFB with self-sealing wound), 14.2% underwent two operations, 22.8% underwent three operations, and 16.7% underwent four or more.…”
Section: Discussionmentioning
confidence: 94%
“…While the rate of second surgery in Shah MA, et al 2013 [48] study was 30%. While Liu, X et al 2022 [49] reported that traumatic cataract was found in 29 (60.4%). 8.3% had one operation (vitrectomy to remove IOFB with self-sealing wound), 14.2% underwent two operations, 22.8% underwent three operations, and 16.7% underwent four or more.…”
Section: Discussionmentioning
confidence: 94%
“…Statistical analyses were performed using the SPSS Statistics version 19 (SPSS Inc., Chicago, IL, USA). A chi-squared test or Fisher test for categorical variables was applied to compare the differences among subjects 8 . Univariate logistics regression was applied to evaluate the associations between risk factors and final BCVA 3 .…”
Section: Methodsmentioning
confidence: 99%